2019
DOI: 10.1007/s11783-019-1121-8
|View full text |Cite
|
Sign up to set email alerts
|

Culturomics and metagenomics: In understanding of environmental resistome

Abstract: Pharmaceutical residues, mainly antibiotics, have been called "emerging contaminants" in the environment because of their increasing frequency of detection in aquatic and terrestrial systems and their sublethal ecological effects. Most of them are undiscovered. Both human and veterinary pharmaceuticals, including antibiotics, are introduced into the environment via many different routes, including discharges from municipal wastewater treatment plants and land application of animal manure and biosolids to ferti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 59 publications
0
36
0
Order By: Relevance
“…Historically, these methods have been used in microbiology, including selective or differential media, microscopy, Gram-staining, and biochemical tests. These methods are sensitive, reliable, inexpensive, and provide qualitative and quantitative results on the bacterial populations ( Nowrotek et al, 2019 ). However, only a small fraction of all microbes can be grown in a laboratory setting.…”
Section: Mining Enzymes From Extreme Environmentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Historically, these methods have been used in microbiology, including selective or differential media, microscopy, Gram-staining, and biochemical tests. These methods are sensitive, reliable, inexpensive, and provide qualitative and quantitative results on the bacterial populations ( Nowrotek et al, 2019 ). However, only a small fraction of all microbes can be grown in a laboratory setting.…”
Section: Mining Enzymes From Extreme Environmentsmentioning
confidence: 99%
“…Based on this legacy, microbial culturomics has emerged as a tool that complements metagenomics data and gives another way to determine composition of microbial populations. Several studies have shown that culture-dependent and culture-independent methods often deliver different results ( Steven et al, 2007 ; Carraro et al, 2011 ; Stefani et al, 2015 ; Nowrotek et al, 2019 ; Rego et al, 2019 ). For example, using 212 different culture conditions, such as temperature, various oxygen levels, and selective media, many researchers have isolated 340 different bacterial species ( Lagier et al, 2012 ).…”
Section: Mining Enzymes From Extreme Environmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…While novel culturing methods can be very diverse ( Pham and Kim, 2012 ; Overmann et al, 2017 ), several still rely on the use of the petri dish. Because of its versatility, the petri dish is still a central tool for the recent field of culturomics, the “extensive assessment of microbial composition by high-throughput culture” ( Greub, 2012 ; Nowrotek et al, 2019 ). Richard Petri’s development of a simple device for culturing bacteria has thus withstood the test of time and remains a protean tool for research, even in the genomic era.…”
Section: Introductionmentioning
confidence: 99%
“…Despite lower sensitivity, cultivation may allow detection of species that are overlooked with molecular tools and offers the opportunity to develop biological resources for functional and genetic studies. Moreover, the integration of cultivation and HTS has allowed a complete survey of microbial diversity, uncovering species that were previously neglected or unknown to science, when applied in samples from different extreme environments (e.g., [ 25 , 26 ]).…”
Section: Introductionmentioning
confidence: 99%